A Toolkit for Modeling and Simulating Cloud Data Storage: An Extension to CloudSim - Saiqin Long; Yuelong Zhao (2012 International Conference on Control Engineering and Communication Technology, 2012)
With the popularity of cloud computing technology, cloud storage technology as a new kind of distributed storage technology is widely used to store and manage massive data. Large-scale data management and analysis is difficult to achieve in complex scenarios. In order to overcome this challenge, we extend the cloud simulation platform CloudSim by adding the file striping and data replica management function, making it into a simulation platform for computing and storage. The expanded CloudSim can be used to implement different data layout and replica management strategy. And it's easily to add functionality to meet other needs. This paper gives a detailed description of the design and proves the significance of it through examples.